2019
DOI: 10.1002/fam.2798
|View full text |Cite
|
Sign up to set email alerts
|

Material properties of clay and lime plaster for structural fire design

Abstract: Summary Clay and lime plaster are traditional surface finish materials used on historic timber walls and ceilings. Today, hardly any fire technical properties or design parameters exist that consider such plasters as fire protection materials for timber structures. This hinders the fire assessment of existing building structures and disadvantages their use in modern design solutions where healthy and sustainable materials are increasingly favoured. This research follows the safety philosophy of EN 1995‐1‐2 to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…It is known that the fire retardant properties of plaster compositions are affected by the density and coefficients of heat capacity and thermal conductivity, depending on the temperature and the nature of the binder and filler of the plaster [46]. To determine the density at which the greatest fire resistance is provided, the temperature curves of clay and lime plaster compositions obtained by fire testing under the standard temperature regime were analyzed [26] (Figure 15).…”
Section: Determination Of the Optimal Density Of The Plaster Compositionmentioning
confidence: 99%
See 2 more Smart Citations
“…It is known that the fire retardant properties of plaster compositions are affected by the density and coefficients of heat capacity and thermal conductivity, depending on the temperature and the nature of the binder and filler of the plaster [46]. To determine the density at which the greatest fire resistance is provided, the temperature curves of clay and lime plaster compositions obtained by fire testing under the standard temperature regime were analyzed [26] (Figure 15).…”
Section: Determination Of the Optimal Density Of The Plaster Compositionmentioning
confidence: 99%
“…It is known that the fire retardant properties of plaster compositions are affected by the density and coefficients of heat capacity and thermal conductivity, depending on the temperature and the nature of the binder and filler of the plaster [46]. To determine the density at which the greatest fire resistance is provided, the temperature curves of clay and lime plaster compositions obtained by fire testing under the standard temperature regime were analyzed [26] (Figure 15). As seen in Figure 15, the graphs for the samples with clay and lime plasters with high density (1610-1800 kg/m 3 ) grow at a higher rate, demonstrating low fire resistance limits compared to the samples with coatings studied in this work, and a lower density (220 to 775 kg/m 3 ).…”
Section: Determination Of the Optimal Density Of The Plaster Compositionmentioning
confidence: 99%
See 1 more Smart Citation
“…The second method of fire protection of metal structures includes plaster compositions with a thickness of 10-60 mm, used in dry rooms (at a relative air humidity of less than 65%), applied on a steel grid and used to increase the fire resistance limit of metal structures up to 2 and more hours. In [15], experiments concerning clay and lime plaster compositions with a high density applied to wooden structures were demonstrated to determine their thermophysical properties under standard temperature conditions. Experimental studies are confirmed by numerical simulation, and the low fire protection efficiency of clay and lime plaster was shown.…”
Section: Introductionmentioning
confidence: 99%